Menakar Perlindungan HAM Dalam Revisi UU Minerba Melalui UN Guiding Principles on Business and Human Rights - Ayu Kholifah (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
The ratification of Law Number 3 of 2020 (Revision of the Mining Law) on June 10, 2020 by President Joko Widodo raised a polemic so that several parties have filed a judicial review of the law. This phenomenon indicates that there are interests that are not accommodated in the Revision. The natural resource business as the sector with the greatest risk of human rights violations is in the spotlight whether the Revision are much better to guarantee human rights protection or not. The UN Guiding Principles on Business and Human Rights (UNGPs) is a recommendation that can be used as a parameter how human rights are protected on the Revision. This research is normative legal research using qualitative descriptive methods by combining statutory approaches and conceptual approaches. The results show that the absence of mandatory regulations and guidelines for human rights protection in domestic business activities is a factor in the low level of human rights protection in the Revision. Human Rights Protections by the State and Human Rights Respects by companies have not been comprehensively regulated, access to recovery for human rights impacts is still not maximal and needs to be developed as recommended in the UNGPs.